The application of flocoumafen as the second generation anticoagulant rodenticide (sgar) on Norway rat (Rattus norvegicus) in Serdang, Selangor - Said, Nadhirah Najwa (2018)
Few species of rodent in Malaysia known as Rattus rattus, Rattus norvegicus and also Rattus argentiventer. This study required to focus more on Rattus norvegicus. Rattus norvegicus is a brown rat, known as a street rat, Norway rat or sewer rat. There are a lot of places that suitable for a rodent to grow their population such as landfill area and dining area. The problem is there is a lot of landfill area in Malaysia. This study is about the efficacy of second-generation rodenticide, Flocoumafen on Rattus norvegicus in Serdang, Selangor. The trapping and bait station technique has been used in this study. Three location of the study had been choose in Serdang. The pre-baiting and post baiting observation is to calculate the population of the rat after the post baiting. Nine bait station has been used to put in the flocoumafen. In this study, we would like to identify the commensal rodent species exists in Sri Serdang, Selangor. Secondly, to evaluate the trapping success of Rattus norvegicus before and after flocoumafen baiting. Lastly, to estimate the population abundant of Rattus norvegicus before and after flocoumafen bait application. The findings of this study are, there is a decreasing number of Rattus norvegicus after the application of flocoumafen in the study area. The population estimation of Rattus norvegicus is reduced from 101 to 75 rat per week after the flocoumafen application and then the capture estimation is decreased from 10.67% to 5.67% maybe because of bait shyness. So, we can use the flocoumafen as the second generation anticoagulant rodenticide to control Rattus norvegicus in Sri Serdang area.